2022
DOI: 10.1038/s41598-022-11180-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental independence of median fins from the larval fin fold revises their evolutionary origin

Abstract: The median fins of modern fish that show discrete forms (dorsal, anal, and caudal fins) are derived from a continuous fold-like structure, both in ontogeny and phylogeny. The median fin fold (MFF) hypothesis assumes that the median fins evolved by reducing some positions in the continuous fin fold of basal chordates, based on the classical morphological observation of developmental reduction in the larval fin folds of living fish. However, the developmental processes of median fins are still unclear at the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…This points to a second and independent function of wnt10a in the transition from an embryonic, purely actinotrichia-based fin fold into unpaired adult fins, which still contain actinotrichia in distal-most regions, while their main mechanical support is provided by bony rays of lepidotrichia. 15,17,56,79 Consistently, at the early stages of metamorphosis, we found wnt10a to be highly expressed in the dermal space of the caudal fin (Figure 5C) and canonical Wnt signal reception in interray domains distal of the lepidotrichia (Figure 6F), where the actinotrichia are located. 56 Interestingly, genetic loss of col9a1c, which is normally expressed in mesenchymal and basal epidermal cells of the forming and regenerating adult caudal fin, leads to aberrant actinotrichia formation/maintenance in distal regions of the outgrowing caudal fins and to later lepidotrichia defects and caudal fin deficiencies 56 very similar to those shown here for the wnt10a mutant (Figure 1H).…”
Section: The Requirement Of Zebrafish Wnt10a For Adult Fin Formation ...supporting
confidence: 77%
See 1 more Smart Citation
“…This points to a second and independent function of wnt10a in the transition from an embryonic, purely actinotrichia-based fin fold into unpaired adult fins, which still contain actinotrichia in distal-most regions, while their main mechanical support is provided by bony rays of lepidotrichia. 15,17,56,79 Consistently, at the early stages of metamorphosis, we found wnt10a to be highly expressed in the dermal space of the caudal fin (Figure 5C) and canonical Wnt signal reception in interray domains distal of the lepidotrichia (Figure 6F), where the actinotrichia are located. 56 Interestingly, genetic loss of col9a1c, which is normally expressed in mesenchymal and basal epidermal cells of the forming and regenerating adult caudal fin, leads to aberrant actinotrichia formation/maintenance in distal regions of the outgrowing caudal fins and to later lepidotrichia defects and caudal fin deficiencies 56 very similar to those shown here for the wnt10a mutant (Figure 1H).…”
Section: The Requirement Of Zebrafish Wnt10a For Adult Fin Formation ...supporting
confidence: 77%
“…11 Furthermore, Wnt/β-catenin signaling, activated by unspecified ligands, was shown to be necessary for regular outgrowth of adult fins in zebrafish 12 and for epithelial patterning and growth in the zebrafish embryonic median fin fold (MFF). 13,14 Here, we identify Wnt10a as being essential both for the maintenance of the larval MFF and for the later, developmentally independent 15 formation of the adult median fins. The wnt10a mutant had been isolated in a phenotype-based forward genetics screen after random chemical mutagenesis and deposited in the ZFIN database as unnamed gene/mutant unm_t30922, displaying embryonic MFF defects.…”
Section: Introductionmentioning
confidence: 84%
“…Careful consideration of the embryonic proximity of the dorsal and caudal fins and their modular relationship may provide a deeper understanding of how these two phenotypes may have simultaneously occurred 12 , 16 , 21 , 29 , 30 . Molecular developmental studies in zebrafish revealed that the mesenchymal cells of the dorsal- and caudal fins are derived from the different levels of somite, but the epithelial cells are connected to each other at the embryonic stage; the epithelial cells form the fin fold and its primordia 31 , 32 . Based on the close embryonic proximity of epithelial cells, it is naturally presumed that both dorsal- and caudal fins are under the influence of the same molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mef2ca gene was also examined in terms of its buffering function in the context of dermal skeleton morphogenesis 36 . Unlike these experimentally derived phenotypic variations, the phenotypic variations in goldfish were established through a process of artificial selection for the stabilization of visually classifiable strains (for example, Ryukin and Ranchu strains) after the fixation of the chdS E127X allele (Abe et al, 2022). Thus, it is reasonable to assume that the ornamental morphologies of established goldfish strains are the consequence of the canalization of morphogenesis [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%